PERANCANGAN MESIN PENEPUNG KULIT DAN BONGGOL JAGUNG - Rezaldi reza; Aldrin (Program Studi Teknik Mesin Fakultas Rekayasa Sistem Universitas Teknologi Sumbawa, 2023)
Utilization of waste corn cobs and corn husks as additional feed ingredients, Livestock includes water content, dry matter, crude protein and crude fiber and crude fiber respectively as follows: 29.54; 70.45; 2.67 and 46.52% in 100% material, this plan aims to produce designs and construction drawings of a strong, sturdy, safe, and efficient corncob and corn husk pulverizing machine. Get results as planned. Get the results of the analysis of the Cob and Corn Skin Penepung Machine. The process of designing the cob and corn husk flour machine is carried out in stages, namely planning and explanation of tasks/functions, product concept planning (working drawings). Technical analysis includes analysis of power, torque that occurs in the axle and frame. The propulsion of the corn husk and cob flouring machine is planned to use an 8.5 HP kobota engine with 2200 Rpm which is designed to produce a capacity of 800 kg/hour with the results of the corn cob and husk flour being adjusted to the filter on the corn cob and corn husk flour machine. Using a sieve size of 1mm. The results of the calculation result in a corn husk and cob flour machine with dimensions of length specifications W x W x H 800 mm x 500 mm x 800 mm using a V-belt and pulley with a 30 mm diameter drive shaft. The frame construction is made of 40x40x3 mm elbow profile with St material and the cover uses an iron plate with a thickness of 2 mm Keywords : Design, flour Machine, Modification